Pathologic complete response despite nodal yield has best survival in locally advanced rectal cancer - Narayanan, Sumana (J Surg Res, 2020)
BACKGROUND: Controversy exists regarding the ability of neoadjuvant chemoradiation (nCR) to diminish lymph node yield (LNY) and how that relationship is influenced by tumor response in patients undergoing proctectomy for locally advanced rectal cancer. STUDY DESIGN: The National Cancer Database was used to identify patients with rectal adenocarcinomas from 2004 to 2014. Patients that received nCR were compared to those that underwent surgery alone. LNY was stratified into <12 and ≥12 groups to determine their differences in stage specific overall survival. RESULTS: Of 56,812 patients 46.5% underwent surgery alone and 53.5% were administered nCR. There were more patients with LNY<12 in the nCR group compared to surgery alone, across all stages (44.1% vs. 36.5%, p<0.001). nCR improved OS regardless of LNY(p<0.001). Although patients with LNY≥12 had improved overall survival, patients that had a pCR achieved the greatest survival. In patients that did not achieve a pCR, LNY≥12 was a marker of improved OS but LNY did not impact OS in patients that attained pCR (p<0.001). CONCLUSIONS: Although nCR diminished LNY, LNY≥12 improved OS demonstrating the importance of quality TME. However, LNY did not impact patients that achieved pCR. These patients, who achieved the best OS, demonstrated that tumors’ biologic response to nCR had the greatest impact on patient outcomes.